Dampak Personal Branding terhadap Personal Image Foodvlogger di Youtube Berdasarkan Perbedaan Generasi Y Dan Z - Mohamad Hadi Prasetyo (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
The purpose of this research is how personal branding can influence personal image with the perceptions of different generations. The development of increasingly sophisticated communication technology has brought major changes to human communication patterns. With the presence of YouTube and the content that is currently busy is culinary world content. Foodvlogger is the name for those who create content in the culinary field on YouTube. Images in the digital world are considered important because they appear to be homogeneous even though they are heterogeneous. Personal image is important for foodvloggers because they appear as individuals who are perceived by their audience. Personal branding that is built is something that can improve your image. The variety of generations that enjoy social media will be a problem in itself, with different generations because there are differences in perceived experiences, there will be differences in perception. This research was designed as a type of survey method where the goal was to test hypotheses. The focus is on explaining the relationships between variables which will ultimately be implemented for two different generations. The results can be discussed as differences in perceptions from generations Y and Z, but because the historical background and social life of the two generations are not too far apart, their assessments are also not too far apart. In other words, the personal branding and personal image of food vloggers are already well embedded in generations Y and Z. Where both generations can accept food vloggers well and see their activities on YouTube well too.